PENGARUH IMPLEMENTASI KEPEMIMPINAN, KEAKRABAN, DAN EKSKLUSIVISME TERHADAP KOMITMEN ORGANISASIONAL STUDI DI UNIVERSITAS NAHDLATUL WATHAN MATARAM - Sofian Hadi (Master of Management, Mataram University, 2017)
The aim of this research: 1) to know the significance influence of Leadership Implementation of Organizational Commitment at the University of Nahdlatul Wathan Mataram, 2) to know the significance influence of Leadership Implementation of Organizational Commitment which is moderated by Familiarity at the University of Nahdlatul Wathan Mataram, and 3) to know the significance influence of Leadership Implementation of Organizational Commitment which is moderated by Exclusivism at the University of Nahdlatul Wathan Mataram. The type of research is causal associative research using census method. The population in the study were all members of the Organization at Nahdlatul Wathan University Mataram with a 86 people The data collection tool used is questionnaire with questionnaire technique and the using Moderator Regression Analysis with backword elimination method. The results showed that : 1) Direct Leadership Implementation can have a positive effect and significant to Organizational Commitment of organization members at Nahdlatul Wathan University Mataram, 2) Familiarity can strengthen the influence of Leadership Implementation on Organizational Commitment of organization members at Nahdlatul Wathan University Mataram, and 3) Exclusivism may weaken the influence of Leadership Implementation or not significantly influence the Organizational Commitment of organization members at Nahdlatul Wathan University Mataram Keywords : Leadership Implementation, Familiarity, Exclusivism, and Organizational Commitment.